Facile Synthesis and Characterization of Au Nanoclusters-Silica Fluorescent Composite Nanospheres. (24th October 2013) - Wang, Huiping; Xu, Chaoyong; Zheng, Chengzhi; Xu, Wei; Dong, Tianjiao; Liu, Kanglei; Han, Heyou; Liang, Jiangong
Abstract : We developed a novel method for the synthesis of Au nanoclusters (NCs) silica fluorescent composite nanospheres by mixing the as-prepared bovine serum albumin (BSA) protected Au NCs with amino-modified silica spheres in acetate buffer solution. The products were characterized by high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), fluorescent microscope imaging (FLMI), and dynamic light scattering (DLS) measurements. The proposed method was simple, efficient, and inexpensive. In addition, the composite nanospheres exhibited favorable water-dispersible, stable, and fluorescent properties, potentially leading to further applications in chemical and biological sensors. A reasonable mechanism was also proposed for the formation of composite nanospheres.